Biology, population dynamics and secondary production of the green crab Carcinus maenas (L.) in a temperate estuary - Baeta, A. (2005)
The biological features, population dynamics and secondary production of Carcinus maenas were studied between June 2003 and June 2004 in four areas within the Mondego estuary, Portugal. Benthic samples were collected monthly, during the night, at high water of spring tides using a 2-m beam trawl, and plankton samples were collected monthly, during the day, at high tide with a Bongo net. Only the first zoeae stage of C. maenas larvae was found in the plankton; it was collected at all sampling stations throughout the year. A continuous pattern of benthic recruitment was observed in the upstream areas of the estuary with the highest peaks occurring in the spring 2004. Females carrying eggs were also caught through the year, although mainly in downstream areas. Juveniles' sex-ratio was favourable to males at almost all the sites sampled. Ventral carapace colour varied between green and orange-red, with the proportion of the green morphotype increasing with the increasing distance from the mouth of the estuary. The proportion of crabs in moult also increased from downstream to upstream areas. For both sexes the crab population showed a similar size structure throughout the year. The upstream areas of the estuary were characterized by the dominance of juveniles, with adults migrating to downstream areas. The average annual production of C. maenas, P (growth production), was estimated at 0.08 g m-2 y-1 AFDW, and the average annual biomass () was estimated at 0.058 g m-2, resulting in a ratio of 1.4.